The application of multivariate statistical process monitoring in non-industrial processes. Issue 4 (4th July 2018) - Bersimis, Sotiris; Sgora, Aggeliki; Psarakis, Stelios
ABSTRACT: Statistical process monitoring (SPM) techniques have been widely used in industry for many decades in order to assess the process stability, as well as the final product quality. Interestingly, SPM techniques have gained popularity in many non-industrial fields providing even more opportunities for research. In this paper, we consider the case of multivariate statistical process monitoring (MSPM) and perform an extensive literature review on MSPM applications in non-industrial fields. More specifically, the aim of this paper is to point out the main non-industrial application fields of MSPM that have appeared in the literature, discuss the main challenges that arise upon applying MSPM outside the industrial environment and provide some thoughts for the future of MSPM outside industry.